ANALISIS FINANSIAL SAYURAN HIDROPONIK DI PT INDMIRA YOGYAKARTA - Anggi Anggelica; Agus Surata; Juarini Juarini (Jurnal Dinamika Sosial Ekonomi, 2018)
This research aims to 1) determine the advantages of three types of vegetables (mustard, lettuce, pakchoy), 2) Analyze the feasibility of three types of vegetables (mustard, lettuce, pakchoy) in PT INDMIRA Yogyakarta in terms of financial. This research used descriptive method. Method of implementation used case study. Analytical techniques were used profit and profit rate. The result of the research showed that the highest profit from the three major vegetable commodities (mustard, lettuce, pakchoy) per month per 16 m2 were lettuce (Rp 601.210), followed by pakchoy (Rp 430.509) and the lowest is mustard (Rp 371.722). the feasibility of these three vegetable commodities (mustard, lettuce, pakchoy) is different. The highest feasibility is lettuce, followed by pakchoy and the lowest is mustard. The hydroponic vegetables business were feasible to cultivate because the value of profit rate is greater than the prevailing interst rate. Keywords: feasibility, profit, profit rate